Exploring Teens as Robot Operators, Users and Witnesses in the Wild - Björling, Elin A.; Thomas, Kyle; Rose, Emma J.; Cakmak, Maya (Frontiers in Robotics and AI, 2020)
As social robots continue to show promise as assistive technologies, the exploration of appropriate and impactful robot behaviors is key to their eventual success. Teens are a unique population given their vulnerability to stress leading to both mental and physical illness. Much of teen stress stems from school, making the school environment an ideal location for a stress reducing technology. Our mixed-methods study \hl{was an attempt to understand teens' operation of, and responsiveness to, a robot only capable of movement compared to a robot only capable of speech.} Stemming from a human-centered approach, we introduce a Participatory Wizard of Oz (PWoz) interaction method that engaged teens as \hl{operators, users, and witnesses} in a uniquely transparent interaction. In this paper we illustrate the use of the PWoz interaction method as well as how it helps \hl{identify engaging robot interactions}. Using this technique, we present results from a study with 62 teens that includes details of the complexity of teen stress and a significant reduction in negative attitudes toward robots after interactions. \hl{We also analyzed the teens interactions with both the verbal and non-verbal robots} and identified strong themes of (1) authenticity, (2) empathy, (3) emotional engagement, and (4) imperfection creates connection. Finally, we reflect on the benefits and limitations of the PWoz method and our study to identify next steps toward the design and development of our social robot.